Monochromatic Blue Light Activates Suprachiasmatic Nucleus Neuronal Activity and Promotes Arousal in Mice Under Sevoflurane Anesthesia - Liu, Daiqiang; Li, Jiayan; Wu, Jiayi; Dai, Jiaqi; Chen, Xinfeng; Huang, Yujie; Zhang, Shuang; Tian, Bo; Mei, Wei (Frontiers in Neural Circuits, 2020)
Background: Monochromatic blue light (MBL), with a wavelength between 400–490 nm, can regulate non-image-forming (NIF) functions of light in the central nervous system. The suprachiasmatic nucleus (SCN) in the brain is involved in the arousal-promoting response to blue light in mice. Animal and human studies showed that the responsiveness of the brain to visual stimuli is partly preserved under general anesthesia. Therefore, this study aimed to investigate whether MBL promotes arousal from sevoflurane anesthesia via activation of the SCN in mice. Methods: The induction and emergence time of sevoflurane anesthesia under MBL (460 nm and 800 lux) exposure was measured. Cortical electroencephalograms (EEGs) were recorded and the burst-suppression ratio (BSR) was calculated under MBL during sevoflurane anesthesia. The EEGs and local field potential (LFP) recordings with or without locally electrolytic ablated bilateral SCN were used to further explore the role of SCN in the arousal-promoting effect of MBL under sevoflurane anesthesia. Immunofluorescent staining of c-Fos was conducted to reveal the possible downstream mechanism of SCN activation. Results: Unlike the lack of effect on the induction time, MBL shortened the emergence time and the EEG recordings showed cortical arousal during the recovery period. MBL resulted in a significant decrease in BSR and a marked increase in EEG power at all frequency bands except for the spindle band during 2.5% sevoflurane anesthesia. MBL exposure under sevoflurane anesthesia enhances the neuronal activity of the SCN. These responses to MBL were abolished in SCN lesioned (SCNx) mice. MBL evoked a high level of c-Fos expression in the prefrontal cortex (PFC) and lateral hypothalamus (LH) compared to polychromatic white light (PWL) under sevoflurane anesthesia, while it exerted no effect on c-Fos expression in the ventrolateral preoptic area (VLPO) and locus coeruleus (LC) c-Fos expression. Conclusions: MBL promotes behavioral and electroencephalographic arousal from sevoflurane anesthesia via the activation of the SCN and its associated downstream wake-related nuclei. The clinical implications of this study warrant further study.